Geographic distribution and damage estimate of white scale of mango in Chiapas, Mexico - López Guillén, Guillermo; Noriega Cantú, David; Urías López, Mario A. (Revista Mexicana de Ciencias Agrícolas, 2017)
The white mango scale (EBM), Aulacaspis tubercularis Newstead (Hemiptera:Diaspididae), is an emerging pest that affects the foliage and commercial value of mango fruits. The geographic distribution and estimation of damages of exotic pests are components that serve in the decision making for the application of control methods. The objective of this work was to determine the geographic distribution and estimate of damages of the EBM in different localities and mango producing municipalities of the state of Chiapas. Samples were taken during two years (2013-2014) in mango orchards of different localities and municipalities to estimate the EBM populations in foliage and fruits. During the two years, EBM populations were detected in almost all localities. In the first year of sampling (2013), the locations with the greatest abundance of EMB in foliage were Orchard Colombia, The Norteña, Ranch Cinco Hermanos, Ranch The Carmen and others, while in the samplings in fruits it was linked to Puerto Madero. In the second year of sampling (2014), the orchard with the highest abundance of EBM in foliage was The Guamuchal and in ruits it was the area between Puerto Arista and Paredon. The municipalities with more EBM in foliage during the two years of sampling were Mapastepec, Escuintla, Tuzantán, Mazatán, Acapetahua and Huehuetán, while in fruits were Mazatan, Tuxtla Chico and Tuzantán. Finally, during the two years of sampling, the mango cultivar with the highest abundance of EBM in foliage was Manililla, and in fruits were Oro and Creole.
Keywords: introduced pests, mango orchards, regions and cultivars